Favre–Racouchot disease: systematic review and possible therapeutic strategies. (7th August 2018) - Paganelli, A.; Mandel, V.D.; Kaleci, S.; Pellacani, G.; Rossi, E.
Abstract: Favre–Racouchot disease (FRD) is a relatively common dermatosis induced by chronic sun exposure. FRD is clinically and histologically characterized by the presence of both comedones and cysts in the context of an elastotic degeneration of the dermis. Those lesions are mainly located in the face, especially in the malar and periorbital areas. Smoking and radiotherapy seem to play a role in the pathogenesis together with UV exposure. The disease affects predominantly the aged population and seems to be a problem of mainly aesthetic concern. No official guidelines are available for the treatment of FRD; most common therapeutic strategies are represented by topical retinoids and laser treatments. The goal of our review was to identify the principal clinical and epidemiological characteristics of FRD and to analyse all the therapeutic strategies available. We also focused our attention on the follow‐up of this particular dermatosis. Our aim was therefore to suggest alternative possible strategies for both the treatment and the follow‐up of these patients. Our data support the efficacy of carbon dioxide laser and topical retinoids in the setting of FRD, but we also suggest considering alternative treatments, such as plasma exeresis. We also recommend planning both a short‐term and a long‐term follow‐up visit, as the majority of relapses is observed after 10–12 months.